Implementation of Mediation and Hakam in Divorce Case in Religious Court - Salman Salman (UIN Sunan Gunung Djati Bandung, 2020)
The resolution of divorce cases in the Religious Courts is still more dominant in the orientation of the litigation process than the non-litigation process, even though the spirit of suppressing the increase in the divorce rate from year to year is one of the missions that the Religious Courts want to achieve. Mediation institutions are actually established to encourage the realization of these ideals, but the results are still far from adequate. In fact, there are other ways in Islamic law that are believed to be effective in reducing the divorce rate, namely hakam. Unfortunately the rights have not been maximally applied by judges in resolving divorce cases at the Religious Courts